2020
DOI: 10.3390/nu12051256
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Regimens Including Probiotics Guide the Individual Development of the Gut Microbiome of Very Low Birth Weight Infants in the First Two Weeks of Life

Abstract: Background: It is unknown to what extent the microbiome of preterm infants is influenced by hospital regimens including the use of different probiotics when it comes to the prevention of necrotizing enterocolitis (NEC). Methods: Prospective controlled multicenter cohort study including very low birth weight infants from three neonatal intensive care units (NICUs) between October 2015 and March 2017. During this time span, stool was sampled every other day during the first two weeks and samples were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 39 publications
4
62
0
1
Order By: Relevance
“…As a well-known probiotic strain, the colonisation of Bifidobacterium can remodel gut microbiota via its inhibiting effect on the colonisation of pathogens [6]. Our results are similar to those in a multicenter cohort study by Kurath-Koller et al [20] that the bacterial load was increased in two weeks' time after probiotics were used in preterm neonates. At the end of follow-up, the biodiversity of the three groups tends to be the same in our study, indicating that the species diversity of gut microbiota grows closer to each other.…”
Section: Discussionsupporting
confidence: 89%
“…As a well-known probiotic strain, the colonisation of Bifidobacterium can remodel gut microbiota via its inhibiting effect on the colonisation of pathogens [6]. Our results are similar to those in a multicenter cohort study by Kurath-Koller et al [20] that the bacterial load was increased in two weeks' time after probiotics were used in preterm neonates. At the end of follow-up, the biodiversity of the three groups tends to be the same in our study, indicating that the species diversity of gut microbiota grows closer to each other.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have reported the effect of gestational age and preterm delivery, on the development of the microbiota, at a general level by using 16S rRNA gene-based sequencing [ 36 , 37 , 38 , 39 , 40 ]. Although some studies have reported low levels or no bifidobacteria in the infants’ gut [ 41 , 42 ], this has been linked to potential methodological biases or geographical differences [ 43 ], whilst most of the studies have found Bifidobacterium among the dominant microbial genera in infants. However, limited information is still available at the bifidobacterial community level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, several factors may affect the gut microbiota of preterm infants, e.g., hospital regimens, even with regard to the putative use of probiotics to blunt NEC. In a very recent publication, Kurath-Koller et al showed the efficacy of some probiotics in improving the gut microbiome of very low birth weight infants during the first two weeks of age, in a triple-center cohort study [ 33 ]. In our mono-centric study, the very low birth weight had an impact on the fecal metabolome of both healthy and NEC-1 children, but not on their gut microbiota nor on their microbiome.…”
Section: Discussionmentioning
confidence: 99%